Hadith #3602 - Sunan Abi Dawud - Abdullah bin 'Ubaidullah b. Abi Mulayka عبد الله بن عبيد الله بن أبي مليكة; Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Sulaiman bin Harb سليمان بن حرب; Uqba binal-Harith bin 'Amir (Sunan Abi Dawud)
The Prophet (ﷺ) said: The testimony of a nomad Arab against a townsman is not allowable.
Grade: Sahih

Hadith #3603 - Sunan Abi Dawud - Abdullah bin 'Ubaidullah b. Abi Mulayka عبد الله بن عبيد الله بن أبي مليكة; Ahmed bin 'Abdullah أحمد بن عبد الله بن أبي; al-Harith bin 'Umayr Abu الحارث بن عمير أبو عمير; Ayoub al-Sakhtiyani أيوب السختياني; Uqba binal-Harith bin 'Amir; Uthman bin Muhammad (Sunan Abi Dawud)
“I married Umm Yahya daughter of Abu Ihab. A black woman entered upon us. She said that she had suckled both of us. So I came to the Prophet (ﷺ), and amentioned it to him. He turned away from me. I said (to him): Messenger of Allah! she is a liar. He said: What do you know? She has said what she has said. Separate yourself from her (wife).
Grade: Sahih